2015
DOI: 10.1111/lam.12420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Listeria monocytogenes from three countries and antibiotic resistance differences among countries and Listeria monocytogenes serogroups

Abstract: A total of 104 Listeria monocytogenes isolates from 330 fish samples from three countries were characterized by multiplex PCR for serogrouping and virulence markers determination and tested for antibiotics resistance. A 53·8% of the isolates belonged to serogroup 1/2a, 3a; 32% belonged to 1/2b, 3b, 7; 14·4% belonged to 4b, 4d, 4e and 1% belonged to 1/2c, 3c. All isolates exhibited resistance to at least one antibiotic but the resistance rates varied among countries. The isolates exhibited high resistance to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
4
20
4
Order By: Relevance
“…Our results revealed that the serotypes of lineage II (1/2a, 1/2c, 3a) are most frequently present in clinical and seafood isolates. Similar findings have also been reported elsewhere (Ebner et al, 2015;Kanki, Naruse, Taguchi, & Kumeda, 2015;Leong, Alvarez-Ord oñez, & Jordan, 2014;Miya et al, 2010;Obaidat, Bani Salman, Lafi, & Al-Abboodi, 2015;Vitas, Garcia-Jalon, & Aguado, 2004).…”
Section: Listeria Spp and Listeria Monocytogenes In Cooked Rte Seafosupporting
confidence: 89%
“…Our results revealed that the serotypes of lineage II (1/2a, 1/2c, 3a) are most frequently present in clinical and seafood isolates. Similar findings have also been reported elsewhere (Ebner et al, 2015;Kanki, Naruse, Taguchi, & Kumeda, 2015;Leong, Alvarez-Ord oñez, & Jordan, 2014;Miya et al, 2010;Obaidat, Bani Salman, Lafi, & Al-Abboodi, 2015;Vitas, Garcia-Jalon, & Aguado, 2004).…”
Section: Listeria Spp and Listeria Monocytogenes In Cooked Rte Seafosupporting
confidence: 89%
“…), as well as high levels of resistance to penicillin, erythromycin and vancomycin when recovered from fish sources (Obaidat et al . ). This could be due to not only uncontrolled use of antimicrobials in the given area but also evaluation criteria applied in the studies.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, L. monocytogenes isolates recovered from foods (Jamali et al 2015) have been reported to have high levels of resistance to ampicillin (20Á9%) and penicillin (16Á3%). Studies showed resistance to penicillin when isolates from dairy foods were tested (90%) (Harakeh et al 2009), as well as high levels of resistance to penicillin, erythromycin and vancomycin when recovered from fish sources (Obaidat et al 2015). This could be due to not only uncontrolled use of antimicrobials in the given area but also evaluation criteria applied in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sterile swab was used to inoculate the mixture evenly on Mueller-Hinton agar and antibiotics transferred on the agar using a disc dispenser after which they were incubated for 24 hours at 37˚C. The inhibition zones were measured to the nearest mm and the values were interpreted as "Resistant (R), Intermediate (I) or Susceptible (S)" using the standards recommended by CLSI [37] for Staphylococci [38].…”
Section: Antibiotic Susceptibility Testing Of Isolatesmentioning
confidence: 99%